The State in Africa : the Politics of the Belly - (:unkn) unknown (My University, 2009)
The State in Africa is one of the important and compelling texts of comparative politics and historical sociology of the last twenty years. Bayart rejects the assumption of African 'otherness' based on stereotyped images of famine, corruption and civil war. Instead he invites the reader to see that African politics is like politics anywhere else in the world, not an exotic aberration.Africans themselves speak of a 'politics of the belly' - an expression that refers not only to the necessities of survival but also to a complex array of cultural representations, notably those of the 'invisible' world of sorcery. The 'politics of the belly' attests to a distinctively African trajectory of power that we need to understand as part of a long-term historical development.While acknowledging the insights of Western social scientists from Weber to Foucault, Bayart never loses sight of the realities of African politics and social life and he is careful to allow African voices - from the 'small boy' in the street to the 'big men' in the presidential palaces - to speak for themselves.This new edition of Bayart's classic book includes a new introduction on Africa in the world today.This book has established itself as an indispensable text on the state and politics in Africa. It also provides a nuanced reading of what we have come to call 'development' and opens the way for a more general reflection on the invention of politics in African and Asian societies.
Keywords: African Research